2014
DOI: 10.1503/cmaj.141005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lung-protective ventilation with lower tidal volumes on clinical outcomes among patients undergoing surgery: a meta-analysis of randomized controlled trials

Abstract: Interpretation:Anesthetized patients who received ventilation with lower tidal volumes during surgery had a lower risk of lung injury and pulmonary infection than those given conventional ventilation with higher tidal volumes. Implementation of a lung-protective ventilation strategy with lower tidal volumes may lower the incidence of these outcomes. Abstract Research E102CMAJ, February 17, 2015, 187(3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…It is important to note that in these animal experiments the time-dependent MB P was applied when the lungs were still clinically normal (41,(111)(112)(113). Thus these studies support the clinical evidence that early application of low VT and PEEP will reduce ARDS incidence in high-risk patients undergoing surgery or receiving care in an ICU (58,119).…”
Section: Synthesis Reviewsupporting
confidence: 65%
See 3 more Smart Citations
“…It is important to note that in these animal experiments the time-dependent MB P was applied when the lungs were still clinically normal (41,(111)(112)(113). Thus these studies support the clinical evidence that early application of low VT and PEEP will reduce ARDS incidence in high-risk patients undergoing surgery or receiving care in an ICU (58,119).…”
Section: Synthesis Reviewsupporting
confidence: 65%
“…These studies illustrate four key concepts: 1) mortality in patients with established ARDS remains unacceptably high even with low VT ventilation (105,131,134); 2) improperly adjusted mechanical ventilation can exacerbate EALI in patients at high risk and thus increase ARDS incidence (73); 3) preemptive application of a protective ventilation strategy in this same high-risk group of patients can significantly reduce ARDS incidence (7,35,49,50,52,53,58,66,72,119); and 4) the optimally protective breath necessary to block progressive ALI remains to be determined.…”
Section: Mechanical Ventilation and The Incidence Of Ardsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23][24] Multiple studies in patients in the ICU have shown that preemptive protective MV can reduce ARDS incidence. Th is has been shown with conventional MV (CMV) using a combination of LV t , positive endexpiratory pressure (PEEP), and recruitment maneuvers (RMs), 22 including a preemptive randomized clinical trial demonstrating that ARDS incidence can be reduced in high-risk patients in the ICU.…”
Section: Patients In the Icumentioning
confidence: 99%